No difference in antidepressant prescription in rheumatoid arthritis and controls. Results from a population-based, matched inception cohort. (4th May 2022) - Pedersen, JK; Andersen, K; Svendsen, AJ; Hørslev-Petersen, K
Abstract : Objective: Depression occurs at least two times more often in rheumatoid arthritis (RA) patients than in controls, but little is known about the treatment of depression in RA. The primary objective of this study was to compare the 1 year period prevalence of antidepressant prescription in patients with RA versus controls. Method: We included a retrospective inception cohort of 509 patients with incident RA and 2545 frequency-matched population controls ascertained from 1995 to 2002. The cohort was followed until 31 December 2017 and linked with nationwide Danish registers. From the Danish National Prescription Register, we obtained information on redeemed prescriptions of antidepressants (Anatomical Therapeutic Chemical code N06A). Results: We did not demonstrate significant differences in the 1 year period prevalence ratios and the incidence rate ratios for either antidepressant prescription or the frequency of hospital admissions with depressive episode. The most frequent indication for antidepressant prescription in patients with RA was depression. Cox regression analyses showed no association between RA and antidepressant prescription. Conclusion: We found no significant differences in the occurrence of antidepressant prescription in patients with RA versus matched controls. The main indication for antidepressant prescription in RA was depression.